(untitled) (The Pakistan Development Review, 2000)
This paper examines the intertemporal behaviour in consumption for Turkey which has been experiencing high and chronic inflation since the late 1970s. The Frisch demand system is used to estimate three separate but inextricably intertemporal elasticities: intertemporal price elasticities of demand, commodity-specific intertemporal elasticities, and the intertemporal substitution elasticity of consumption. Our main result is that the Turkish households are reluctant to move their expenditures on non-durable goods from the current period to the next period, regardless of how high nominal interest rates are. This interesting result shows that the consumption behaviour in Turkey has been mainly shaped by uncertainty created by inflationary process and the tendency towards hedging against inflation.